Radiation-induced morphea of the breast: a case report - Cheah, Nellie LC (BioMed Central, 2008)
Radiation-induced morphea (RIM) of the breast is a rare complication of radiotherapy. It is disfiguring, painful and defeats the purpose of achieving a good cosmesis in breast-conservation surgery. This report describes a severe case of RIM in a breast cancer patient together with photographic illustrations of the serial changes over time and histopathology slides. A review of the literature is provided.